Comparison of remote and local postconditioning against hepatic ischemic-reperfusion injury in rats - Yasojima,Edson Yuzur (2021)
ABSTRACT Purpose: The aim of this study is to compare the hepatic protective effect of both remote and local postconditioning (POS). Methods: Twenty-eight Wistar rats were assigned into four groups: sham group(SHAM), ischemia-reperfusion group (IR), local ischemic POS group (lPOS) and remote ischemic POS group (rPOS). Animals were subjected to liver ischemia for 30 min. Local ischemic POS group consisted of four cycles of 5 min liver ischemia, followed by 5 min reperfusion (40 min). Remote ischemic POS group consisted of four cycles of 5 min hind limb ischemia, followed by 5 min hind limb perfusion after the main liver ischemia period. After 190 minutes median and left liver lobes were harvested for biochemical and histopathology analysis. Results: All the conditioning techniques were able to increase the level of bothglutathione reductase and peroxidase, showing higher values in the rPOS group when compared to the lPOS. Also, thiobarbituric acid reactive substances were higher in all intervention groups when compared to SHAM, but rPOS had the lower rates of increase, showing the best result. The histopathology analysis showed that all groups had worst injury levels than SHAM, but rPOS had lower degrees of damage when compared to the lPOS, although it was not statistically significant. Conclusion: Remote postconditioning is a promising technique to reduce liver ischemia-reperfusion injury, once it increased antioxidants substances and reduced the damage.